(untitled) (Global Journal of Medical Research, 2023)
Background In ALS patients diaphragmatic dysfunction is usually assessed by pulmonary function testing PFTs that requires patient cooperation Evidence suggest that diaphragm ultrasound DU can be utilized as an alternative to PFTs to detect reduced diaphragmatic motility in ALS patients This study aimed to verify the agreement between the results obtained by DU with those obtained by PFTs in both standing-up and supine positions Methods Twenty nine spinal ALS and thirteen healthy controls were studied in standing up and lying 30 supine position All subjects performed PFTs and DU to assess of diaphragmatic excursion delta-thickness between end inspiration and end expiration T and the thickening fraction TF